The reinvention of Spain nation and identity since democracy - Balfour, Sebastian; Quiroga, Alejandro, 1972-; Oxford eBooks (Oxford : Oxford University Press, 2007)
Unravelling the fierce debate in Spain about nation and identity which is still causing division today, this book looks at the debate and its role as part of a wider global process in which traditional identities are evolving rapidly, or being challenged.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nationalism -- Spain; Spain -- Politics and government -- 1975-; Electronic books